2010
DOI: 10.1345/aph.1p380
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes: The Impact of Clinical Pharmacy Services Integrated into Medical Homes on Diabetes-Related Clinical Outcomes

Abstract: The integration of clinical pharmacy services into safety net medical homes was associated with improvement in clinical outcomes of patients with diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 19 publications
1
41
0
Order By: Relevance
“…Previous studies have shown that patients who received pharmacist-managed care demonstrated improved A1c values. [7][8][9][10][11][12][13] Increased A1c is associated with increased costs per hospitalization, and these inpatient costs account for the major expenditure in health spending for patients with diabetes in the United States.…”
Section: ■■ Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies have shown that patients who received pharmacist-managed care demonstrated improved A1c values. [7][8][9][10][11][12][13] Increased A1c is associated with increased costs per hospitalization, and these inpatient costs account for the major expenditure in health spending for patients with diabetes in the United States.…”
Section: ■■ Discussionmentioning
confidence: 99%
“…Minority populations, especially Hispanic patients, have a higher prevalence of diabetes, worse glycemic control, poor adherence, and more complications than non-Hispanic white patients with diabetes. 11 Previous studies have observed that Hispanics have a lower rate of diabetes-related hospitalizations. 11,19,20 Multiple factors contribute to this finding, such as cultural stigma associated with the hospital setting.…”
Section: Limitationsmentioning
confidence: 98%
See 3 more Smart Citations